We have to prove that a^3 - b^3 = (a - b)(a^2 - ab + b^2)

This is not the right factorization a^3 - b^3 = (a - b)(a^2 + ab + b^2)

To prove this start with the right hand side

(a - b)(a^2 + ab + b^2)

=> a*(a^2 + ab + b^2) - b*(a^2 + ab + b^2)

=> a^3 + a^2*b + a*b^2 - a^2*b - a*b^2 - b^3

=> a^3 + a^2*b - a^2*b + a*b^2 - a*b^2 - b^3

=> a^3 - b^3

**This proves that a^3 - b^3 = (a - b)(a^2 + ab + b^2)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now